Peptic ulcer disease: one in five is related to neither Helicobacter pylori nor aspirin/NSAID intake. Issue 8 (27th August 2013) - Charpignon, C.; Lesgourgues, B.; Pariente, A.; Nahon, S.; Pelaquier, A.; Gatineau‐Sailliant, G.; Roucayrol, A.‐M.; Courillon‐Mallet, A.; ,
Summary: Background: The proportion (and even the reality) of peptic ulcer disease (PUD) not related to H. pylori or NSAID/aspirin is debated. Aim: To analyse the current epidemiological and clinical characteristics of peptic ulcer disease in French general hospitals. Methods: Prospective multicentre study of patients with peptic ulcer disease in 32 French general hospitals over 1 year. H. pylori status was assessed by histology, and/or serology and/or C13‐urea breath test. NSAID/aspirin intake (obtained by direct interview) and data about concomitant diseases were collected on the day of endoscopy. Results: Nine hundred and thirty‐three patients were selected during the year 2009. After exclusion of 118 patients with only erosive duodenitis, 24 with major missing data, 13 with other causes of ulcer and 65 negative for H. pylori by only one test, 713 patients were classified into four groups: 285 (40.0%) had only H. pylori infection; 133 (18.7%) only gastrotoxic drugs; 141 (19.8%) had both and 154 (21.6%) neither H. pylori infection nor gastrotoxic drug intake ('idiopathic ulcers'). Patients with idiopathic ulcers differed in many ways both from H. pylori and NSAID/aspirin groups. However, multivariate analysis identified only three independent predictors: age, French metropolitan origin and the presence of comorbidities. Conclusion: In a general hospital‐based population in France, peptic ulcer disease appears idiopathic in a fifth of cases.